2023
DOI: 10.1097/mej.0000000000001043
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of pulse CO-oximetry to evaluate blood carboxyhemoglobin level: a systematic review and meta-analysis of diagnostic test accuracy studies

Mathilde Papin,
Chloé Latour,
Brice Leclère
et al.

Abstract: Carbon monoxide (CO) poisoning is one of the most common causes of poisoning death and its diagnosis requires an elevated carboxyhemoglobin (COHb) level. Noninvasive CO saturation by pulse oximetry (SpCO) has been available since 2005 and has the advantage of being portable and easy to use, but its accuracy in determining blood COHb level is controversial. To evaluate the accuracy of SpCO (index test) to estimate COHb (reference test). Systematic review and meta-analysis of diagnostic test accuracy (DTA) studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In blood, COHb is measured either non-invasively through a pulse CO-oximeter, which determines the amount of CO bound to Hb through optical measurement (SpCO), or invasively by blood sampling and determination of COHb through blood gas analyser (25,26). Despite the low-cost, non-invasiveness and timeefficiency in obtaining results, CO monitors and pulse-oximeters are known to have poor sensitivity, especially in the lower COHb concentration range, thus potentially leading to false negatives or falsely low COHb levels (27)(28)(29). One of the main reasons for the inaccurate measurements is the measurement principle of those monitors, which is spectrophotometry.…”
Section: Current Cohb Measurement Methodsmentioning
confidence: 99%
“…In blood, COHb is measured either non-invasively through a pulse CO-oximeter, which determines the amount of CO bound to Hb through optical measurement (SpCO), or invasively by blood sampling and determination of COHb through blood gas analyser (25,26). Despite the low-cost, non-invasiveness and timeefficiency in obtaining results, CO monitors and pulse-oximeters are known to have poor sensitivity, especially in the lower COHb concentration range, thus potentially leading to false negatives or falsely low COHb levels (27)(28)(29). One of the main reasons for the inaccurate measurements is the measurement principle of those monitors, which is spectrophotometry.…”
Section: Current Cohb Measurement Methodsmentioning
confidence: 99%
“…Research by Piatkowski (2009), and Feiner (2013) has proven that the Radical-7 monitor accurately detects hypoxia in the blood and accurately detects carboxyhemoglobin [10], [11]. Although some studies have not fully confirmed the accuracy of this device, the benefits of a device that can detect CO poisoning early and non-invasively cannot be denied [12].…”
Section: Spco Indexmentioning
confidence: 99%